Seasonal Surface Loading Helps Constrain Short‐Term Viscosity of the Asthenosphere. Issue 5 (15th March 2018) - Clarke, Peter J.
Abstract: Earth materials may display a range of rheological behaviors at different depths and over different timescales. The situation is particularly complex for postseismic relaxation in the uppermost mantle and lower crust, where it can be difficult to distinguish widespread viscous behavior from earthquake afterslip or localized deformation in shear zones over timescales of weeks to decades. By analyzing geodetic observations of seasonal surface mass loads and Earth's surface deformation in response, Chanard et al. (2018, https://doi.org/10.1002/2017GL076451) have established a globally averaged lower bound of 5 × 10 17  Pa s for the transient viscosity of a Burgers‐rheology asthenosphere. This implies that lower viscosities inferred by some studies of postseismic relaxation must result from local departures from this global value, or be an artifact of additional afterslip or shear zone deformation. Key Points: Chanard et al. (2018 ) find globally averaged transient asthenospheric viscosity is at least 5e17 Pa s Lower values found by postseismic studies must arise from localized anomalies or misinterpretation of afterslip or shear zone motion Longer time series and finer spatial detail of surface mass loads are needed to tighten this constraint and improve depth resolution